4,5-Dihydro-1,2,3-oxadiazole: A Very Elusive Key Intermediate in Various Important Chemical Transformations - Banert, Klaus; Singh, Neeraj; Fiedler, Benjamin; Friedrich, Joachim; Korb, Marcus; Lang, Heinrich (Chemistry : a European journal, 2015)
4,5‐Dihydro‐1,2,3‐oxadiazoles are postulated to be key intermediates in the industrial synthesis of ketones from alkenes, in the alkylation of DNA in vivo, and in the decomposition of N‐nitrosoureas; they are also a subject of great interest for theoretical chemists. In the presented report, the formation of 4,5‐dihydro‐1,2,3‐oxadiazole and the subsequent decay into secondary products have been studied by NMR monitoring analysis. The elusive properties evading characterization have now been confirmed by 1H, 13C, and 15N NMR spectroscopy, and relevant 2D experiments at very low temperatures. Our experiments with suitably substituted N‐nitrosoureas using thallium(I) alkoxides as bases under apolar conditions answer important questions on the existence and the secondary products of 4,5‐dihydro‐1,2,3‐oxadiazole. Short‐lived! 4,5‐Dihydro‐1,2,3‐oxadiazole is generated by treatment of N‐(2‐chloroethyl)‐N‐nitrosourea with thallium alkoxides at low temperatures, but it is not formed by nucleophilic dealkylation of the corresponding N‐methyloxadiazolinium salt. Even at −90 °C, 4,5‐dihydro‐1,2,3‐oxadiazole cannot be detected directly. However, it was identified by analysis of its decay products, acetaldehyde, ethylene oxide, and diazomethane (see scheme).